Recent advances in the 18-electron complex transition metal hydrides of Ni, Fe, Co and Ru - Humphries, Terry; Sheppard, Drew; Buckley, Craig (2017)
Metal hydrides have received much attention due to the flourishing concept of a hydrogen economy. In addition, recent studies of metal hydride materials have shown that technological implementation of these compounds not only lies in the storage of hydrogen, but for a range of multi-functional applications; including, smart optical windows, energy storage materials in fuel cells for both stationary and mobile devices, and as thermal energy storage materials for concentrating solar thermal plants. This review concentrates on the molecular structures, thermodynamic properties and other physical properties of the complexes of [NiH4]4-, [FeH6]4-, [CoH5]4- and [RuH6]4-. The synthesized derivatives of these compounds have also been reviewed to give a full overview on the advancement of these systems and will allow for a fresh prospective for future studies to fully understand the physical and chemical nature of these complex transition metal hydrides.